دﻻﻟﺔ اﻟﺘﻮظﯿﻒ اﻟﻠﻮﻧﻲ ﻓﻲ ﺷﻌﺮ ﻏﺎدة اﻟﺴﻤﺎن (Journal of the College of Education for Women, 2019)
This research tackles the semantic function of colors in the poetry of Gada Al Samman, in the introduction the research explores the difference in the semantic colors for people and the function of these colors in arising the feelings for the human spirit and its influence on that spirit. The research tackles the poems of this poetess that are full of symbolic colors that convey positive and negative meanings related to the poetess herself. In addition the research shows the functions of colors in her poetry through the compatibility of colors by employing colors in her poetry in terms of compatibility with the vision of community to denote colors. Beside using the function of colors contrast by employing the colors in different meaning and function. And the function of gradient through the gradients or mentioning color feature. And denote intermingling chromatography and interventions, with the stated examples which confirm these meanings.